2016
DOI: 10.5194/acp-16-3311-2016
|View full text |Cite
|
Sign up to set email alerts
|

Polar stratospheric cloud evolution and chlorine activation measured by CALIPSO and MLS, and modeled by ATLAS

Abstract: Abstract. We examined observations of polar stratospheric clouds (PSCs) by CALIPSO, and of HCl and ClO by MLS along air mass trajectories, to investigate the dependence of the inferred PSC composition on the temperature history of the air parcels and the dependence of the level of chlorine activation on PSC composition. Several case studies based on individual trajectories from the Arctic winter 2009/2010 were conducted, with the trajectories chosen such that the first processing of the air mass by PSCs in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…6d-f) shows very good agreement for the first activation phase. Nakajima et al (2016) also reported very good agreement of model and observations during this phase. HCl along the trajectories deviates from the observations after a couple of days.…”
Section: Modeling Heterogeneous Chemistrysupporting
confidence: 73%
“…6d-f) shows very good agreement for the first activation phase. Nakajima et al (2016) also reported very good agreement of model and observations during this phase. HCl along the trajectories deviates from the observations after a couple of days.…”
Section: Modeling Heterogeneous Chemistrysupporting
confidence: 73%
“…A detailed discussion of the rationale behind these choices can be found in Wohltmann et al (2013) The treatment of conditions where both NAT and STS clouds are allowed to form has changed compared to Wohltmann et al (2013). Since mixed NAT/STS clouds are commonly observed (e.g., Pitts et al, 2011), they can now form in the model to allow for a more realistic behavior; see Nakajima et al (2016) for details.…”
Section: Model Setupmentioning
confidence: 99%
“…Inner and outer edges (at least 5 • apart from each other) of the polar vortex were defined by local maxima of the isentropic potential vorticity gradient with respect to equivalent latitude only when a tangential wind speed (i.e., mean horizontal wind speed along the isentropic potential vorticity contour; see Eq. 1 of Tomikawa and Sato, 2003) near the vortex edge exceeds a threshold value (i.e., 20 m s −1 ; see Nash et al, 1996, andTomikawa et al, 2015).…”
Section: Sepmentioning
confidence: 99%